Water Trading: Innovations, Modeling Prices, Data Concerns. (4th January 2019) - Colby, Bonnie; Isaaks, Rowan
Abstract: This article examines policy innovations and data concerns related to water trading in Colorado, and develops econometric models of transactions occurring over two distinct time periods. The Punctuated Equilibrium Theory (PET) of policy adaptation is used to examine shifts in Colorado water trading policy paradigms. Creating better policy frameworks for water trading is a key concern for agricultural, urban, and environmental water interests, given hotter temperatures and more variable precipitation patterns in the western U.S. Contractual arrangements of varying types are being used to engage farmers in providing reliable water supplies for ecosystem and urban needs through changes in farm water use practices. While various pieces of information about changes in water use can be gleaned from public databases, transaction price information is notably lacking. Recent Colorado policy innovations related to water trading emphasize reducing on‐farm consumptive use and making water available for other purposes without permanently drying up irrigated cropland. The use of econometric models analyzing water rights transactions provides insight into how changes in key external factors affect transaction prices. The econometric models developed here focus upon Colorado's urbanizing Front Range and examine the effect of demographics, housing prices, drought indicators, and agricultural profitability on prices at which water is traded. Volume traded, drought measures, housing prices, alfalfa prices, and water source characteristics are statistically significant in these models. The article concludes by discussing factors that contribute to water trading policy innovations and the broader relevance of Colorado's innovative trading arrangements to water management challenges in arid regions.